2001
DOI: 10.1017/s0001924000092046
|View full text |Cite
|
Sign up to set email alerts
|

Flow regimes associated with yawed rectangular cavities

Abstract: The present work is concerned with the aerodynamics of the turbulent boundary-layer flow over yawed rectangular cavities with the focus on the steady and unsteady pressures generated by the interaction. Cavities with a planform aspect ratio of 4-85 and streamwise length to depth ratios from 1 to 3 were studied experimentally in a low-speed wind tunnel. The results indicated three main types of cavity flows. The shear layer bridges the cavity for small angles between mean flow direction and minor ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The two microphones used for analysis were located at the centre of the cavity base and on the working section surface 126 mm upstream of the cavity centre to be used as a reference signal for tunnel noise. Previous studies by Johnston et al [13] and Czech et al [14] have shown that this type of microphone can be successfully used to analyse the frequency spectrum of the fluctuating pressure field when mounted flush with the surface.…”
Section: Microphone Measurementsmentioning
confidence: 99%
“…The two microphones used for analysis were located at the centre of the cavity base and on the working section surface 126 mm upstream of the cavity centre to be used as a reference signal for tunnel noise. Previous studies by Johnston et al [13] and Czech et al [14] have shown that this type of microphone can be successfully used to analyse the frequency spectrum of the fluctuating pressure field when mounted flush with the surface.…”
Section: Microphone Measurementsmentioning
confidence: 99%
“…As discussed in detail in Chapters 3 and 4, experimental measurements of the flow field [50], [71], [72], and [73].…”
Section: Discussionmentioning
confidence: 99%
“…A yawed rectangular cavity means the flow are parallel to the planform of a cavity, but the chordwise direction of the cavity has an angle, β , with respect to the freestream direction [7]. An asymmetric flow pattern inside the cavity was observed [8]. Lada & Kontis [9] showed the yaw angle either disturbs the shear layer or changes the flow type, resulting in attenuation of self-sustained oscillations.…”
Section: Introductionmentioning
confidence: 99%